2011
DOI: 10.1371/journal.pone.0023548
|View full text |Cite
|
Sign up to set email alerts
|

Condensin I Recruitment to Base Damage-Enriched DNA Lesions Is Modulated by PARP1

Abstract: Condensin I is important for chromosome organization and segregation in mitosis. We previously showed that condensin I also interacts with PARP1 in response to DNA damage and plays a role in single-strand break repair. However, whether condensin I physically associates with DNA damage sites and how PARP1 may contribute to this process were unclear. We found that condensin I is preferentially recruited to DNA damage sites enriched for base damage. This process is dictated by PARP1 through its interaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…1 ) [ 10 ]. Consistent with this, another major SMC proteincontaining complex, condensin I , which interacts with PARP1 and a subset of BER factors and participates in BER/SSB repair in human cells [ 15 ], is also preferentially recruited to high input-power [ 12 ] (Fig. 1 ).…”
Section: Introductionsupporting
confidence: 52%
“…1 ) [ 10 ]. Consistent with this, another major SMC proteincontaining complex, condensin I , which interacts with PARP1 and a subset of BER factors and participates in BER/SSB repair in human cells [ 15 ], is also preferentially recruited to high input-power [ 12 ] (Fig. 1 ).…”
Section: Introductionsupporting
confidence: 52%
“…We attempted to identify which cohesin subunit may be responsible for directing cohesin recruitment to damage sites. For example, for condensin I, another SMC complex, we found that the chromosome-targeting domain in the hCAP-D2 subunit possesses damage site targeting activity (36). Thus, we first determined the effect of depletion of one cohesin subunit on the recruitment of other subunits in the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Laser damage induction and image analysis were carried out essentially as described previously (35,36). In brief, 532 nm of the second harmonic of a pulsed Nd:YAG laser beam (ϳ2 to 3 J/pulse energy after objective; ϳ4-to 6-ns pulse duration; 7.5 Hz; Quantronix-Continuum Lasers, La Mesa, CA) was focused through a 100ϫ Ph3 UPlanFI oil objective lens (numerical aperture [NA], 1.3; Olympus) on a microscope (model IX81; Olympus).…”
Section: Methodsmentioning
confidence: 99%
“…An independent study using HeLa cells reported that condensin I is involved in DNA single-strand break (SSB) repair, possibly through its interaction with poly(ADP-ribose) polymerase 1 (PARP-1) and the base excision repair factor XRCC1 (Heale et al 2006). PARP-1 appears to contribute to the retention, but not the initial recruitment, of condensin I to DNA damage sites (Kong et al 2011).…”
Section: Dna Damage Response and Repairmentioning
confidence: 99%